Socioeconomic Challenges for the Wild Harvested Seaweed Sector Development: The Value Chain Mapping and Strategies for Its Institutionalization - Ahila M. S; Neha Wajahat Qureshi; M. Krishnan; Ananthan P. S; Jhonson B; Badri Narayanan Gopalakrishnan (SocioEconomic Challenges, 2025)

(untitled)
Socioeconomic challenges such as limited income for harvesters, lack of market integration, and absence of organized institutional frameworks hinder the sustainable development of the wild-harvested seaweed sector in India. Analyzing the value chain and identifying strategies for its institutionalization can help mitigate these socioeconomic challenges by improving market linkages, reducing price exploitation, and empowering primary producers. This study surveyed 185 actors in the seaweed value chain in Tamil Nadu during 2022 to assess their socioeconomic conditions, market practices, and institutional support. Structured interviews captured data on demographics, income sources, species collected, sales channels, and perceptions of market fairness and government support. Statistical tools such as descriptive analysis, trend analysis, cost-benefit analysis, marketing efficiency tools, and rank-based quotient were used to analyze the results, supported by value chain diagrams and flow models. The findings revealed that most fisherfolk engaged in seaweed collection were women (58%). About 63% of seaweed harvesters were literate, more than half (60%) belonged to the middle-age group (36-55 years), and 60 percent had seaweed collection as their main occupation. The average annual income of a seaweed harvester is ₹ 88,870. The results highlighted a fragmented value chain involving harvesters, agents, and processors, with price spreads exceeding 73% and marketing efficiencies as low as 0.04, 0.36, and 0.13 — indicating significant exploitation and inefficiencies. The absence of collective bargaining mechanisms and formal institutions further exacerbates these challenges. However, patterns such as community clustering and willingness to form cooperatives signal potential for institutional intervention. The study recommends forming Farmer Producer Organizations (FPOs) under Pradhan Mantri Matsya Sampada Yojana (PMMSY) to streamline the wild seaweed value chain, improve bargaining power, and institutionalize market access. Ultimately, this research contributes to reducing socioeconomic challenges in the wild-harvested seaweed sector by offering data-driven strategies to strengthen institutional frameworks and improve livelihoods for coastal communities.